Differential diagnosis of retinal capillary hemangiomas and vasoproliferative tumors - V. V. Neroev; T. N. Kiseleva; A. Yu. Novikova; M. V. Ryabina; P. A. Ilyukhin; K. A. Ramazanova (Российский офтальмологический журнал)
Purpose. To propose the major differential diagnostic criteria of retinal capillary hemangioma (RCH) and vasoproliferative tumor (VPT) aimed at increasing the efficiency of the diagnosis of these diseases.Material and methods. A comprehensive ophthalmologic examination off 19 (26 eyes) patients, aged 19 to 66 (ave. 31.89 ± 11.30 yrs), with vascular neoplasms of peripheral localization included, beside the standard techniques, fundus photoregistration, fluorescent angiography (FAG), optical coherence tomography of the retina and a combined ultrasound testing using B scanning, echographic densitometry, colour Doppler imaging (CDI), and pulse Doppler imaging.Results. Based on the analysis of the clinical picture and the results of the tests performed, the following differential diagnostic criteria were proposed: the age at which RCH and VPT developed, their localization in the eye fundus, and the value of the maximal systolic blood flow velocity in the central vein of the retina.Conclusion. Differential diagnostics of RCH and VPT requires combined approaches and should take into account, in addition to case history and the clinical picture, also the results of instrumental testing techniques: FAG, echography and CDI.